Penerapan Aktivitas Jalan Pagi Terhadap Tekanan Darah Pada Penderita Hipertensi Lanjut Usia Di Desa Bendungan Kabupaten Sragen - Nunung Tri Wijayanti; Norman Wijaya Gati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Hypertension is now a global problem because its prevalence continues to increase in line with lifestyle changes. Blood pressure that continues to increase causes the heart's workload to become excessive, triggering damage to blood vessels, heart failure, kidney failure, and blindness. Hypertension can be treated with non-pharmacological techniques, one of which is with morning walks. Purpose: to determine the effect of implementing morning walks on blood pressure in elderly people with hypertension in Bendungan Village, Sragen Regency. Method: This research method is a case study and descriptive research using pretest and posttest observation sheets. In this case study, the researcher used a tensimeter to measure the respondent's blood pressure, carried out for 30 minutes a week (frequency 4 times). Results: The results of the implementation showed that there was a different decrease in blood pressure between respondent 1 and respondent 2 after implementing morning walks for 30 minutes 4 times a week. Both respondents were categorized as grade 2 hypertension decreasing to degree 1 hypertension. Conclusion: The conclusion from the application results is that the rate of decrease in blood pressure in Mrs. M is greater, namely systolic pressure of 24 mmHg diastolic 1 mmHg while Ny. W decreased systolic pressure 15 mmHg diastolic 6 mmHg.